Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Keaktifan Dan Hasil Belajar Siswa Kelas VII Pada Pembelajaran IPS di MTsn 9 Kediri - Shandy Santria; Dita Hendriani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research was conducted to find out whether jigsaw type cooperative learning can overcome the problems that exist in students in the form of lack of activeness and also learning outcomes. The subjects sampled in this study were students of class VII E as many as 31 students and class VII G as many as 30 students. The data collection method uses quantitative methods. This research design uses class action experimental research. Class VII E as a control class by applying a lecture or conventional learning model, while class VII G as an experimental class applied the jigsaw type cooperative learning model. This research was conducted for three meetings in each class. The results obtained from this study were that the jigsaw type cooperative learning gained an advantage by getting an activeness score of 86 and learning outcomes of 83.33 in the experimental class. While the learning model with a lecture or conventional model is only able to get an average score of 79.97 and an average value of learning outcomes worth 76.45 in the control class. Therefore, it can be concluded that the jigsaw type cooperative learning model is able to influence students' activeness and learning outcomes.